Adaptación social y accidentes del trabajo - Neves, Isodro (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
In comparing two matched groups of workers, those with a high incidence of accidents and those without accidents, it is suggested that, as groups, they show a set of significant differences in terms of their social adaptation at work as well as outside of the work setting. A scheme of the possible relations which link social maladaptation at work with that in the home is attempted.